At will or not at will: Electrophysiological correlates of preparation for voluntary and instructed task-switching paradigms - Chen, Poyu; Hsieh, Shulan (Psychonomic bulletin & review, 2015)
The present study investigated whether the advanced reconfiguration processes of the voluntary switching (VTS) paradigm were different from those of the instructed task switching (ITS) paradigm by examining event-related potentials (ERPs) in a within-subjects design. Of importance, given that effector-to-task mapping might lead to differential preparatory strategies, two effector-to-task mapping groups were studied: the hand-to-task (HAND) and finger-to-task (FINGER) groups. Intriguingly, we found the increased posterior negativity for voluntary switch (and/or increased posterior positivity for voluntary repeat) was exclusive to the HAND group, whereas the increased switch-related late posterior positivity in the ITS paradigm was independent of the effector manipulation. Moreover, the lateralized readiness potentials (LRP) and the mu and beta motor-related amplitude asymmetries indicated that the differential switch-related modulations were not the byproduct of hand-specific preparation. The advanced preparatory strategies in the VTS and ITS paradigms are discussed.